Protective role of eurycoma longifolia jack root extract against high-fat diet induced testicular damage in sprague-dawley rats - Al-Ani I.M.; Ku-Zaifah N.; Al-Joufi F.A.; Mokhtar R.H.; Talib N.A.; Faisal G.G. (EManuscript Technologies, 2024)
Indexed by SCOPUS/ERA